2010
DOI: 10.1128/jcm.01600-10
|View full text |Cite
|
Sign up to set email alerts
|

Differential Circulation of Streptococcus pneumoniae Serotype 6C Clones in Two Israeli Pediatric Populations

Abstract: We genotyped Streptococcus pneumoniae serotype 6C (Sp6C) isolates collected from Jewish and Bedouin children in southern Israel during the decade before vaccination. Sp6C constituted 8.2% of the presumed Sp6A isolates. All of the Sp6C clonal clusters were associated with serogroup 6, mainly Sp6A. Different clonal distributions were found in the two subpopulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Genotyping methods showed the same trend. Previous studies from our group have already shown the differential circulation of non-PCV7 clones among Jewish and Bedouin children in AOM cases (8,26,28). The current study expands this observation also to IPD cases.…”
Section: Discussionsupporting
confidence: 71%
“…Genotyping methods showed the same trend. Previous studies from our group have already shown the differential circulation of non-PCV7 clones among Jewish and Bedouin children in AOM cases (8,26,28). The current study expands this observation also to IPD cases.…”
Section: Discussionsupporting
confidence: 71%
“…Serotype 6C strains share more multilocus sequence typing alleles with serotype 6A strains than either serotype 6B or 19A strains in the www.mlst.net database [23], providing indirect evidence that the serotype 6C capsular locus preferentially inserts into the serotype 6A background. The circulation of some of these serotype 6C clones can vary by population and location [24][25][26][27]. In Spain, two-thirds (142 of 213) of the serotype 6C strains causing IPD were related to a single clonal group (ST224-complex) [27].…”
Section: Molecular Epidemiology Of Serotype 6cmentioning
confidence: 99%
“…A striking clonal segregation was found between the two study populations; e.g., ST6984, the major S. pneumoniae serotype 6D clone, which constituted 31% of the strains, was found only among Bedouin children, whereas ST8599, which constituted 16% of the strains, was found mostly (16/17, 94%) among Jewish children. The differential clonal distribution between the two study populations was already shown by us for additional serotypes (13,(18)(19)(20), suggesting that lifestyle and microenvironment are major determinants in child-to-child transmission of pneumococci.…”
mentioning
confidence: 87%